Measurement of Brain Activity Rate Based on Electroensefalographical Signals on Smokers - Herry Setiawan (Jurnal Inotera, 2018)
Indonesia as a country with 255,182,144 people (Central Bureau of Statistics, 2015) with the number of smokers reached 46.16 percent in the third rank with the largest number of smokers in the world after China and India, there are some elements in cigarettes one of them is nicotine, it will be one of the addictive additives. It's why smokers want to continue smoking cigarettes on a regular basis. It bounds to the brain receptors and in other organs. Increased activity in the orbitofrontal area of the cortex occurs when a smoker wants a cigarette, while in the prefrontal cortex experiences an increase in activity when smokers smoke cigarettes. Increased activity in the area will produce electrically along the scalp that can be measured using Electroencephalography (EEG). The voltage difference of the ion current will give the addiction level information to the cigarette so it can be classified. Classification is done in 4 classes namely low dependence, Moderate dependence and high dependence. From the results of the study we found that the level of brain activity of the frontal cortex increased. 52% of the 40 sampled data showed the highest increase in activity by reaching 53.17% in the highly dependent addiction category.